True or false:A linear binomial has a degree of 0

A trinomial has a degree of 2

A constant has a degree of 1

A cubic monomial has a degree of 3

I will mark as the top answers of you help me!

Answers

Answer 1
Answer:

Answer:

The degree of a binomial is zero. The product of two binomials is not a polynomial. The sum of two polynomials is a polynomial. A monomial containing ^2 has a degree of three

The degree of the polynomial is found by looking at the term with the highest exponent on its variable(s). Examples: 5x2-2x+1 The highest exponent is the 2 so this is a 2nd degree trinomial.

Names of Degrees

Degree Name Example

0 Constant 7

1 Linear x+3

2 Quadratic x2−x+2

3 Cubic x3−x2+5

The degree of a cubic monomial is three. A quadratic polynomial is a trinomial. The degree of a binomial is two.

Step-by-step explanation:


Related Questions

a man has some hens and cows. if the number of heads is 48 and number of feet is 140. find the number of hens.
Kathleen bought 8.3 ounces of walnuts. The next day, she used 1.7 ounces of them in a recipe. How many ounces does she have left?
The graph shows the data points in the table and the exponential regression model associated with the data. A 2-column table with 5 rows. The first column is labeled days after treatment with entries 2, 4, 6, 8, 10. The second column is labeled number of weeds with entries 100, 26, 6, 2, 1. A graph shows days after treatment labeled 1 to 11 on the horizontal axis and number of weeds on the vertical axis. A line shows a downward trend. Based on the graph of the regression model, which is true? The number of weeds is decreasing by a multiplicative rate. The number of weeds is increasing by a multiplicative rate. The number of weeds is decreasing by an additive rate. The number of weeds is increasing by an additive rate.
solve quadratic equation by factoring How do you do it 3k^2 + 72 = 33k
I don’t know how to answer this

The graph of y = x 2 has been translated 7 units to the left. The equation of the resulting parabola is _____.

Answers

Answer:

y = (x+7)^2

Step-by-step explanation:

Horizontal translation:

if y =f(x) , then y = f(x+h) is horizontal translation.

The translation h moves the graph to the left when h is the positive value and to the right when h is negative.

As per the statement:

Given the graph:

y=x^2

It has been translated 7 units to the left

By definition:

h = 7 units > 0

then, the equation becomes;

y = (x+7)^2

Therefore, the equation of the resulting parabola is, y = (x+7)^2

Assuming you meant the equation y=x^2, the translated equation would be Y=(x+7)^2

Y = x - 2 and y=-2x +7

Answers

\huge\boxed{\boxed{\bold{(3, 1)}}}

\hrulefill

I'm assuming you need to find the solution to this system of equations (where the lines intersect).

We can use the substitution method to solve this system. Take the value of y from the second equation and substitute it into the first:

-2x+7=x-2

Add 2x to both sides of the new equation:

7=3x-2

Now add 2 to both sides of the equation:

9=3x

Divide both sides by 3:

\boxed{3}=x

Now let's solve for y by substituting the known value of x into the first equation:

y=3-2

Simplify using subtraction:

y=\boxed{1}

This means our solution is:

\large\boxed{(3, 1)}

Answer:

x = 3, y = 1

Step-by-step explanation:

Solve the following system:

{y = x - 2 | (equation 1)

y = 7 - 2 x | (equation 2)

Express the system in standard form:

{-x + y = -2 | (equation 1)

2 x + y = 7 | (equation 2)

Swap equation 1 with equation 2:

{2 x + y = 7 | (equation 1)

-x + y = -2 | (equation 2)

Add 1/2 × (equation 1) to equation 2:

{2 x + y = 7 | (equation 1)

0 x+(3 y)/2 = 3/2 | (equation 2)

Multiply equation 2 by 2/3:

{2 x + y = 7 | (equation 1)

0 x+y = 1 | (equation 2)

Subtract equation 2 from equation 1:

{2 x+0 y = 6 | (equation 1)

0 x+y = 1 | (equation 2)

Divide equation 1 by 2:

{x+0 y = 3 | (equation 1)

0 x+y = 1 | (equation 2)

Collect results:

Answer: {x = 3, y = 1

A recipe includes 2 cups of flour and two thirds cup of milk. write the ratio of the amount of flour to the amount of milk as a fraction in simplest form.

Answers

(2)/( (2)/(3) ) = 2* (3)/(2) = (6)/(2)(/2) = \boxed{(3)/(1)}
Flour:Milk
2:2/3
both multiply by 3
6:2
both divide by 2
3:1

What will most likely be Wilson's approximate science score if he does science homework for 6 hours a week?33 points
42 points
52 points
55 points

Answers

The right answer for the question that is being asked and shown above is that: "52 points." the choice that will most likely be Wilson's approximate science score if he does science homework for 6 hours a week is 52 points

Answer:

the answer is 55.. this SHOULD NOT BE A VERIFIED ANSWER!! I KNEW I SHOULD'VE WENT WITH MY FIRST THOUGHT INSTEAD. I DONT EVEN KNOW WHY I PAY FOR THIS APP. IT HELPS MAYBE 50% OF THE TIME. ALWAYS DIFFERENT ANSWERS EVERYWHERE. GRRRRR

The power generated by a wind turbine depends on the wind speed . The expression 800 v^3 gives the power in watts for a certain wind turbine at wind speed v in meters per second . If the wind speed triples , by what factor does the power generated by the wind turbine increase ? 2) Can you write the expression 49x^2y^2z^2 using only one exponent ? Show how or explain why not ?

Answers

Power  = 800v³

If the speed triples, v is replaced by 3v.

  Power = 800*(3v)³ =  800*27v³ = 27*(800v³)

 The power increases by 27 times.


2)  49x²y²z² 

The expression can be written using one exponent

49x²y²z² = 7²* x² *y² * z²   = (7xyz)²

                                                 =  (7xyz)²
1. it would increase by 27 times
in other words, 3^3 times

2. You can rewrite the expression using one exponent because each variable is being squared and multiplied by each other
if you had 3^2 x 4^2 it would be 144 (9 x 16)
same as if you had (3 x 4)^2 which is 12^2, which is also 144
the expression would be (7xyz)^2

Convert 72°F to °C (to the nearest tenth) using one of the following formulas: F = 9/5xC + 32 or C = (F - 32) x 5/9.

Answers

If you would like to convert 72°F to °C using one of the following formulas, you can do this using the following steps:

C = (F - 32) * 5/9
C = (72 - 32) * 5/9
C = 40 * 5/9 
C = 22.2°C

The correct result would be 22.2°C.
First set up the equation:
C=(F-32)*(5)/(9)
Then substitute in known values:
C=(72-32)*(5)/(9)
and solve for C
C=40*(5)/(9)
C=22.22